DAMPAK SOSIAL PROGRAM PENGELOLAAN SAMPAH BERBASIS KOMUNITAS DI PULAU PRAMUKA, KEPULAUAN SERIBU - Nike Vonika (Politeknik Kesejahteraan Sosial Bandung, 2022)
The success of an empowerment program in the community is when there is a continuation of the program even though the termination has been carried out. There are various things prepared in ensuring the sustainability of a program, one of which is related to the presence of local champions. The community-based plastic waste management program on Pramuka Island, Thousand Islands, which was initiated in 2020, is still continuing today. This program was previously assisted by the Get Plastic Indonesia Foundation which was supported by PT. Astra and in collaboration with the Green Literacy House. After more than two years after the mentoring process was completed, the Green Literacy House as a local organization continues to be committed to continuing this program in the local area and has even replicated it to the surrounding islands in the Thousand Islands. The social environmental impact of the sustainability of this program is felt by the local community. Through this research using a qualitative approach, the social impacts arising from the program mentioned above are described. First, there is an economic impact on tourism activists and the local community because this program is a pilot program for areas that have succeeded in managing plastic waste at the source, thereby increasing the number of tourist visits, especially for educational tourism. Apart from that, maintaining the territorial waters around the island also has a good economic impact on fishermen. Furthermore, the social impact, with the existence of waste management facilities on Pramuka Island, the level of knowledge of residents regarding waste management is better so that it also raises awareness of residents to use plastic wisely